Predlog Direktive o ustreznih minimalnih plačah v EU z vidika slovenske ureditve - Bobovnik, Andraž (Delavci in delodajalci, 2021)
Proposal for a directive on adequate minimum wages in the European Union presented on 28th of October 2020 is acceptable for the Republic of Slovenia both from the content and legal framework point of view. Current Slovenian regulation in areas of labor relations, minimum wage, collective bargaining, surveillance, sanctions and social dialogue is predominantly in accordance with measures proposed in the directive. Additional obligations though could arise in areas of fostering collective bargaining, social dialogue and data collection and reporting.
Keywords: collective bargaining; delovno pravo; European Commission; European Pillar of Social Rights; Evropska komisija; Evropski steber socialnih pravic; kolektivna pogajanja; minimalna plača; minimum wage; social dialog; socialni dialog